Self-reported mood sensitivity to pollen, seasonality of mood and depressive symptoms in a college sample. - Kosak, Alice; Rohan, Kelly J; Nillni, Yael I; Postolache, Teodor T (International Journal of Child & Adolescent Health, 2010)
This study is in part a replication of a prior study by Guzman and colleagues that examined mood sensitivity to pollen and seasonality of mood in a convenience sample of African and African American college students in Maryland. The current study used a sample of primarily Caucasian students (n = 444) at a northeastern college. Participants completed a battery of questionnaires including the Seasonal Pattern Assessment Questionnaire (SPAQ) from which the Global Seasonality Score (GSS) was calculated, diagnosis of Seasonal Affective Disorder (SAD) or sub-syndromal SAD (S-SAD) was derived, a seasonal pattern (high pollen vs. no pollen) identified, and self-reported mood changes during high pollen counts obtained. Unique to this study, participants completed two questionnaire measures of current depressive symptoms, the Structured Interview Guide for the Hamilton Depression Rating Scale, Seasonal Affective Disorder, Self Rating Version (SIGH-SAD-SR) and the Center for Epidemiological Studies-Depression Scale (CES-D), and the month of assessment was recorded. Contrary to expectation, seasonality of mood was not different between participants who endorsed mood sensitivity to pollen and those who did not. In addition, mood sensitivity to pollen was not significantly related to SAD/S-SAD high pollen pattern status vs. no diagnosis. In participants with mood sensitivity to pollen there was no difference in depression scores on the SIGH-SAD-SR and CES-D when assessed during months when atmospheric pollen is undetectable vs. months with detectable atmospheric pollen counts. Ethnic differences, latitude, statistical error, or unmeasured variables may explain differences between Guzman et al's study and this negative report.